FROM A MODEL OF CONCURRENCY TO A TEST MODEL: A GRAPH TRANSFORMATION BASED APPROACH - CHAOUI, A.; SAIDOUNI, D.; BOUARIOUA, M.; BEKRAR, S.; KERKOUCHE, E. (Courrier du Savoir, 2014)
Maximality-based Labeled Transition Systems (MLTS) is semantic model for true concurrency. In other hand Mixed Refusal Graphs  (MRG)  are models  for  formal  testing.  In  this  paper, we  propose  an  approach  to  transform  an MLTS model  to  an equivalent  MRG  model.  Since  the  input  and  output  models  are  graphs,  we  use  graph  transformation  to  perform  this transformation automatically. So, we propose  two meta-models; one for the input model and the other for the output model. Then,  based  on  these meta-models we  propose  a  graph  grammar  that  deals with  the  transformation  process.    The meta- modeling tool ATOM3  is used. Our approach is illustrated through an example.